Students’ Dominant Motivation In Learning Reading At The Tenth Grade Of SMAN 1 Candung - Mutiara Dewi Cahya; Merry Prima Dewi (CV. Ulil Albab Corp, 2022)
The purpose of this study was to describe the highest motivation in learning to read in class X SMAN 1 Candung. The research question in this study is what is the dominant motivation in learning to read in grade 10 of SMAN 1 Candung. This study uses quantitative descriptive with class X students as the research population. The research sample amounted to 74 students who were selected through total sampling technique. Data collection is done through a questionnaire. Questionnaires were used to obtain data on students' motivation in learning to read comprehension. The type of questionnaire used is a closed questionnaire. That is a questionnaire presented to students, so students only need to provide a checklist for each question/statement. In the questionnaire there are 18 questions written in English and translated into Indonesian to make it easier for students to understand and answer the questions. The results showed that the highest aspect selected was intrinsic motivation (84%) and the lowest was extrinsic motivation (78%). Based on the data, it can be concluded that intrinsic motivation is the dominant motivation in learning to read in class 10 of SMAN 1 Candung.